Characterization of a novel cell wall hydrolase CwlE involved in Bacillus thuringiensis subsp. israelensis mother cell lysis - Huang, Lixin; Han, Guangjie; Crickmore, Neil; Li, Chuanming; Xia, Yang; Song, Fuping; Xu, Jian (Frontiers in Microbiology, 2023)
Cell wall hydrolases are ubiquitous among spore-form bacteria and essential for mother cell lysis. In this study, a novel cell wall hydrolase gene cwlE involved in mother cell lysis was characterized from Bacillus thuringiensis subsp. israelensis (Bti) strain Bt-59. cwlE was specifically expressed in Bti and located in the large plasmid carrying the insecticidal genes. The encoded CwlE protein consists of a MurNAc-LAA domain and two highly conserved catalytic residues (E26 and E151). The recombinant CwlE-His protein was able to digest the cell wall of Bti, indicating that CwlE is an N-acetylmuramoyl-L-alanine amidase. Transcriptional analysis indicated that cwlE began to express at the early stage of stationary phase and was controlled by SigE. Single mutation of cwlE gene delayed Bti mother cell lysis, while double mutation of cwlE and sigK completely blocked Bti mother cell lysis. After exposure to UV light to deactivate the crystal proteins, the level of decrease of insecticidal activity against mosquito larvae of Bt-59 (ΔcwlE-sigK) was less than that observed for Bt-59the insecticidal activity of the double mutant strain against the larvae of Culex pipiens and Aedes albopictus increased by 36.35% and 26.08% compared to the wild-type strain. This study elucidates the mechanism of Bti mother cell lysis and provides an effective strategy for mosquito control using Bt products with increased persistence.